Human Resource Management in Improving Teacher Professionalism in International Standard Schools - Firnanda; Sigit Priyo Sembodo (Wasatha: Jurnal Studi Islam dan Humaniora, 2023)
Good Human Resource Management greatly determines the quality of madrasas, and greatly influences the improvement of teacher competence and professionalism. This competence can be achieved if the madrasah head as a manager is able to manage teachers in an educational institution so that they have competence in increasing their professionalism. The research problems in this thesis are (1) How does MSDM work in increasing the professionalism of Human Resources in this case teachers (2) How does the process of recruiting, developing and evaluating teacher performance or supervision and monitoring in HRM work to improve the professionalism of teacher HR. This research is a descriptive field research with a qualitative approach. Data obtained through observation, interviews, and documentation. Data were analyzed by interactive analysis from Milles and Hubberman, through the stages of data collection, data reduction, data presentation and drawing conclusions. Checking the validity of the data in this study was carried out by testing the credibility (credibility) with the triangulation technique. The results of the study (1) Human resource management at MBI Amanatul Ummah goes according to what has been well organized. (2) (a) The teacher recruitment process at MBI Amanatul Ummah has been carried out in several stages, namely: Checking the required formations, Delivering announcements, Calling or participating in selection, Interviews, Microteaching and then acceptance and placement. (b) the development of teacher human resources is carried out with several programs including: improving education, conducting seminars, workshops and various other trainings. (c) Supervision or assessment of teacher performance and monitoring is carried out through direct evaluation, supervision and assessment.